The China mission advocate - Roberts, Issacher Jacob, 1802-1871; Gützlaff, Karl Friedrich August, 1803-1851; Parker, Peter, 1804-1888 (Missionary periodicals from the China mainland.)
"This rare and valuable...magazine sought to rally support in the United States for the initial efforts of Protestant missionaries in China." Includes letters and reports from I.J. Roberts, Charles Gutzlaff and Peter Parker and others.